PENGARUH STRUKTUR KEPEMILIKAN DAN STRUKTUR DEWAN TERHADAP TINGKAT UNDERPRICING - Fauzan Dicky Hermawan; Sri Handayani (Diponegoro Journal of Accounting, 2018)
The aim of this study is to examine the effect of corporate governance attributes like ownership concentration, institutional ownership, board size of commissioner, and board independent of commissioner on the level of underpricing. This study used firm size, ROA, firm age, and auditor reputation as control variable. This study uses secondary data obtained from the Indonesia Stock Exchange (IDX). The population in this study consists of all IPO firm in Indonesia Stock Exchange for the period 2013 - 2017. Sample determined with purposive sampling method. Total sample of this research is 83 companies. This study used multiple regression analysis for hypotheses testing. The results of this study show that the size of the board of commissioners and board independence of commissioner have significant negative effect on the level of underpricing IPOs firm. This research also shows that the ownership concentration and institutional ownership do not have significant effect on the level of underpricing IPOs firm.